Population-Based Epidemiology and Microbiology of Community-Onset Bloodstream Infections - Laupland, Kevin B. (American Society for Microbiology, 2014)
SUMMARY: Bloodstream infection (BSI) is a major cause of infectious disease morbidity and mortality worldwide. While a positive blood culture is mandatory for establishment of the presence of a BSI, there are a number of determinants that must be considered for establishment of this entity. Community-onset BSIs are those that occur in outpatients or are first identified <48 h after admission to hospital, and they may be subclassified further as health care associated, when they occur in patients with significant prior health care exposure, or community associated, in other cases. The most common causes of community-onset BSI include Escherichia coli, Staphylococcus aureus, and Streptococcus pneumoniae. Antimicrobial-resistant organisms, including methicillin-resistant Staphylococcus aureus and extended-spectrum β-lactamase/metallo-β-lactamase/carbapenemase-producing Enterobacteriaceae, have emerged as important etiologies of community-onset BSI.